ժխտման կարգի ըմբռնման հիմնական հայեցակետերը - Նաիրա Շաչիլվյան (Տաթև գիտակրթական համալիր, ՀՀ ԳԱԱ Հ. Աճառյանի անվան լեզվի ինստիտուտ)
В данной статье рассматриваются основные аспекты трактования сущности отрицания. Категория отрицания анализируется с философской, логической, психологической и лингвистической точек зрений. Отрицание представлено как универсальный феномен, исследования которого в научном плане, можно сказать, безграничны. The following article deals with the interpretation of the essence of negation. It discusses the most significant viewpoints of the analysis of the negation category from philosophical. logical, psychological and linguistical points of view. The negation is presented as a universal phenomenon, which scientific investigations are boundless.
Keywords: Լեզվաբանություն